TYPES OF ARTISTIC REFERENCE: PROBLEMS OF INTERPRETATION - Mehela, Kateryna (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2025)
The article discusses the challenges of translating American influencer slang, with a focus on a self-help book by American blogger and author Tinx (Christina Najjar). It examines key features of influencer discourse-such as informal vocabulary, internet slang, author-coined neologisms, pop culture references, psychology and business terminology. The study argues that influencer slang, deeply embedded in digital culture, functions not only as a means of communication but also as a sociocultural instrument that fosters linguistic innovation and influences contemporary literary styles. The article highlights primary challenges of translating Tinx’s work into Ukrainian, including preserving irony, expressive nuances, and stylistic coherence; handling abbreviations and acronyms; effectively adapting pop culture allusions; and accurately capturing the author’s figurative language and specialized terminology. These intricacies demand a creative translation approach and a thorough grasp of the cultural context embedded in the original text. The study identifies key translation strategies: literal word-for-word translation, descriptive rendering, functional equivalents, transliteration, cultural adaptation, and context-driven combinations of these techniques based on pragmatic objectives. The findings emphasize that successfully translating influencer slang requires a keen awareness of cultural subtleties, language evolution, and the unique stylistic features of the source text. In order to convey Tinx’s signature style-marked by humor, self-irony, and an engaging, colloquial narrative manner – the translator must blend precision with creativity. Beyond linguistic accuracy, the principal objective is to maintain the interactive and casual tone that defines influencer communication. The article provides practical recommendations for translating contemporary non-fiction texts infused with elements of internet culture. ________________ References: • Browko, K. A. (2024). Semantychna koordynata anhliiskoho merezhevoho slenhu. Suchasni doslidzhennia z inozemnoi filolohii, 1(25), 24–32. • Dziubina, O. I. (2016). Struktura, semantyka ta prahmatyka slenhovykh neolohizmiv sotsialnykh merezh Twitter ta Facebook (na materiali anhliiskoi movy) [Avtoref. dys. ... kand. filol. nauk: 10.02.04]. Lvivskyi natsionalnyi universytet imeni Ivana Franka. • Kozubai, I. (2022). Strukturno-semantychni osoblyvosti slenhu sotsialnykh merezh. Aktualni pytannia humanitarnykh nauk, 56(2), 149–153. • Melnytska, O., & Kudelska, O. (2023). Vplyv merezhevoho slenhu na komunikatsiiu na platformakh, zokrema Twitter. Aktualni pytannia humanitarnykh nauk, 65(2), 195–202. • Mehela, K. I. (2024). Movni stratehii influienseriv SShA v epokhu sotsmerezh. In Stan, problemy ta perspektyvy rozvytku nauky, osvity, tekhnolohii i suspilstva: Zbirnyk tez dopovidei mizhnarodnoi naukovo-praktychnoi konferentsii (pp. 20–23). Kremenchuk: TsFEND. • Nikolaieva, T. M. (2019). Leksyko-semantychni aspekty movy sotsialnykh merezh. Zakarpatski filolohichni studii, 9(2), 96–101. • Nikolaieva, T. M. (2019). Osnovni metody perekladu tekstspik (movy sotsialnykh merezh) ukrainskoiu movoiu. Vcheni zapysky TNU imeni V. I. Vernadskoho. Seriia: Filolohiia. Sotsialni komunikatsii, 30(69), 1(1), 156–161. • Bhatia, A. (2023). Digital Influencers and Online Expertise: The Role of Social Media in Shaping Professional and Public Discourse. Routledge. • Crystal, D. (2011). Internet Linguistics: A Student Guide. New York, NY: Routledge. • Eble, C. (1996). Slang and Sociability: In-Group Language among College Students. University of North Carolina Press. • Evans, V. (2017). The Emoji Code: The Linguistics Behind Smiley Faces and Scowls. New York: Picador. • McCulloch, G. (2019). Because Internet: Understanding the New Rules of Language. New York, NY: Riverhead Books. • Seargeant, P., & Tagg, C. (2014). The Language of Social Media: Identity and Community on the Internet. Palgrave Macmillan. • (2023). The Shift: Change Your Perspective, Not Yourself. New York: Simon & Schuster. • Urban Dictionary. (n.d.). Urban Dictionary. Retrieved from https://www.urbandictionary.com • Sprout Social. (n.d.). 130 most important social media acronyms and slang you should know. Retrieved from https://sproutsocial.com/insights/social-media-acronyms